Myth Construction in Baby Diaper Advertisements: A Semiotic Analysis of Mamypoko Pants - Nurul Khairani Abduh; Muhammad Hasyim; Hendri Pitrio Putra; Sairil; Asyrafunnisa; Yohanis Rongre; Ahmad Ridhai Azis (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Advertising serves as a communication medium through which brands promote their products and construct persuasive messages for consumers. Baby product advertisements, such as those for Mamypoko Pants diapers, not only promote but also create myths that shape parents’ perceptions. This study aims to analyze the myths represented in Mamypoko Pants baby diaper advertisements using Roland Barthes’ semiotic theory. The research employed a descriptive qualitative method, with the main data source takenfrom the official Mamypoko Pants YouTube channel. Verbal and nonverbal elements in the advertisements were examined to identify meanings at both denotative and connotative levels, leading to the discovery of underlying myths. The first level (denotative meaning) reveals the product’s identity and the advantages emphasized in the advertisements. Meanwhile, the second level (mythic meaning) shows how culturalvalues are embedded within the ads. The study found that the myths constructed in theMamypoko Pants advertisements include comfort, freedom, excellence, and happiness, all of which work together to persuade consumers. This study contributes to the understanding of how semiotic analysis can uncover socio-cultural meanings in contemporary advertising, particularly within Indonesia’s consumer culture.